Hempstead family papers - Smith, Ambrose C.
Genealogical material concerning the Hempstead family of Connecticut and New York. Includes a deed, wills, a book written by Ambrose C. Smith titled Memorials of the Life and Character of Mary Manuel Lisa (1870), photographs, and other papers. Also includes a notebook containing photocopies of deeds, wills, biographical essays, genealogical data, printed material, and letters written by Henry T. Cook while aboard the frigate Constitution in 1862 and by Octavia W. (Lorrain) Cook.
In part, photocopies.
Library of Congress Prints and Photographs Division.
Family of Robert Hempstead who is associated with the founding of Hempstead, N.Y., and New London, Conn.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room.
Keywords: Cook, Henry T. -- Correspondence; Cook, Octavia W., -- 1811- -- Correspondence; Lisa, Mary Manuel, -- 1782-1869.; Hempstead family; Constitution (Frigate); Genealogy -- Connecticut; Genealogy -- New York (State)